A letter to Isaac Tomkins and Peter Jenkins on primogeniture (Pickering, 1835)
Timothy Winterbottom could be a pseud. - Isaac Tomkins and Peter Jenkins are pseudonyms of Henry Peter Brougham (Baron Braugham and Vaux). - Pamphlet volume.